Impactos das atividades antrópicas sobre a comunidade dos macroinvertebrados bentônicos do Rio Cuiabá e Várzea Grande - MT - Lima, João Batista (2002)
The benthonic macroinvertebrates community has been widely used to evaluate the effects of the anthropic activities on the aquatic ecosystems, but in brazil the studies on the taxocenosis of the macroinvertebrates are scarce, particularly for large rivers crossing metropolitan regions and therefore under urban impacts. The distribution of the macroinvertebrates as well the physical and chemical parameters of the water was studied along the Cuiaba River, between the cities Varzea Grande and Cuiaba. It is noteworthy that these two cities throw out domestic sewage and industrial effluents into the river. The study was conducted during the periods of rainy and dry seasons in the years of 1999 and 2000. During this time the closing of the storage dam of Manso River was completed. This river is one of the main affluents of the Cuiabá River, upstream to the studies region. The sampling was made at six sites in both margins using artificial substrates exposed during six weeks. The resultes shoed differences in the taxocenotic structure of the macroinvertebrate community, and in the physical and chemical parameters of the water. These differences were related to the urban impact and to the closing of dam. The left margin in station 1 has been the best distribution standard of benthonic macroinvertebrates in relation of the others places, it was reflected by the indices of diversity. Oligochaeta and Chironomidae larvae were dominants along the river, however Chironomidae was more abundant in dry seasons and Oligochaeta in rainy seasons.